2007
DOI: 10.4161/psb.2.2.3616
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Signal as a Rapid Long-Distance Information Messenger After Local Wounding of a Plant?

Abstract: A series of works have described an important role of chemical signaling compounds in generation of the stress response of plants in both the wounded and distant undamaged plant tissues. However, pure chemical signals are often not considered in the fast (minutes) long-distance signaling (systemic response) because of their slow propagation speed. Physical signals (electrical and hydraulic) or a combination of the physical and chemical signals (hydraulic dispersal of solutes) have been proposed as possible lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In our previous studies, we observed that fast electrical signal (induced by a propagating hydraulic signal through activation of mechano‐sensitive stretch‐activated channels) may trigger systemic stomatal and photosynthetic responses of tobacco plants and short‐term chemical defense‐related (accumulation of ABA and jasmonic acid (JA)) signaling pathways in tobacco (Hlaváčková et al 2006; Hlaváčková and Nauš 2007). Chloroplast movement is closely linked to photosynthetic efficiency.…”
mentioning
confidence: 99%
“…In our previous studies, we observed that fast electrical signal (induced by a propagating hydraulic signal through activation of mechano‐sensitive stretch‐activated channels) may trigger systemic stomatal and photosynthetic responses of tobacco plants and short‐term chemical defense‐related (accumulation of ABA and jasmonic acid (JA)) signaling pathways in tobacco (Hlaváčková et al 2006; Hlaváčková and Nauš 2007). Chloroplast movement is closely linked to photosynthetic efficiency.…”
mentioning
confidence: 99%
“…used stressor for inducing VP in a wide variety of plants, including barley, 37 faba bean, 37 soybean, 38 tobacco, 39 sunflower, 40 mimosa, 11,41,42 tomato, 6,43 Bidens pilosa, 44,45 pumpkin, 11,46 wheat, 47 and pea. 26,30,31 Mechanical injury also can induce VP.…”
Section: Introductionmentioning
confidence: 99%
“…Stahlberg and Cosgrove () rejected the chemical agent hypothesis as their experiments using only pressure steps could recapitulate VPs without wounding and therefore excluded a wounding substance being present. However, a hormone such as jasmonate may either already be present or could be quickly synthesized (Hlavackova and Nauš, ; Mousavi et al ., ; Farmer et al ., ), and may not require wounding per se . During wounding, ions and chemicals stored within the vacuole could be released into the surrounding tissue and the vasculature, when the cell is damaged (Malone, ).…”
Section: Discussionmentioning
confidence: 99%